Evaluation Study Between Traditional and Recent Laser Treatments in Eye Disease - Hassan Jalal Aziz (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
Three distinct ocular treatment methods are well-known: conventional, clinical, and laser. Patients were recruited from three centres: Sharp vision at PAR hospital, IBN SINA in CMC hospital, and Consulting in Rezgary hospital, and were followed for 180 days. A total of 3035 eye sufferers were observed, and it was determined that 22% (673) of patients chose laser therapy with the Argon (146 patients) and Yag kinds (345 patients). Seventy-eight per cent of respondents favoured conventional clinical care. Several (2364) were referred for clinical treatment, while others received traditional medicine from the centre and village populations. This diversity in therapeutic approaches is related to three factors: 1. The population's level of education; 2. Economic sustainability; and 3. Satisfaction in the medicinal kind.